Upaya Guru Pendidikan Agama Islam dalam Mengatasi Kesulitan Membaca Al-Qur’an di SMA Mandala Trikora - Rika Auliya; Hasruddin Dute; Moh. Ali Mahmudi; Muhamad Thoif (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to: (1) identify and describe the picture of the difficulty of reading the Qur'an among students at SMA Mandala Trikora Jayapura, and (2) identify and describe the efforts of Islamic Religious Education teachers in overcoming the difficulty of reading the Qur'an among students at SMA Mandala Trikora Jayapura. These objectives were formulated to gain a deeper understanding of the condition of students' ability to read the Qur'an and the strategies used by teachers to improve this ability. The type of research used in this study is qualitative research. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study show that: (1) The picture of the difficulty of reading the Qur'an among students at SMA Mandala Trikora Jayapura is still quite diverse. Some students have difficulty pronouncing several hijaiyah letters, such as the letters 'ain, tsa, qof, shin, shad, ghain, and kha. Furthermore, students also experience difficulties in understanding punctuation marks, such as tasydid and long punctuation marks (mad), and are not yet fully able to apply the rules of tajweed, such as idgham and ikhfa'. Some students were even found to be unable to read the Qur'an well, such as not being fluent, not being able to pronounce the letters correctly, and not adhering to the rules of tajweed. (2) Efforts made by Islamic Religious Education teachers to overcome these difficulties in reading the Qur'an include extracurricular Qur'an reading activities held every two weeks, namely on Wednesdays and Fridays after school hours, with a duration of approximately one to two hours per meeting. Furthermore, teachers also implement a peer tutoring method and conduct regular evaluations of students' Qur'an reading to gradually improve their reading skills.